A Production and operations management study on The Food People, Inc. - Bacud, Marie Joanne (College of Engineering, 2003)
Businesses aim to set established objectives, at this era of global competition, not only to survive in the industry but also to lead in the industry relative to its competitors. Competition in the market sets a need for companies to cater to customer demand. It is also competition that companies aim to prove their production and operations by managing and integrating their operations and systems to comply with their long-term goal. The Food People, Incorporated (TFPI), the company under study, is a manufacturer of ice cream, the brand name of which is known as Fruits in Ice Cream (FIC). It caters to the international (exporting mainly to Japan and US), as well as the local market. The company sought to make ice cream based on international standards in terms of quality and flavor. To do so, the company has to run its manufacturing excellence in full extent that is, to have a very efficient and productive system. In line with improving the production and operations of TFPI, a study was conducted to improve the systems of the said company. The study aims to determine long-term goals or strategic plans and competitive priorities of the company to be able to evaluate the current system of the company. The study also aims to identify the major problems that the company encounters regarding their production and other operations to formulate recommendations on how to address the problems. Documentation of the company's product and process design, capacity, demand management, aggregate plans, inventory system, supply chain management, material requirements planning, and scheduling were done by the group to evaluate the current system of the company. After the documentation of the system, the three major problems were identified to be the lack of mathematical forecasting technique used, unoptimized production plan during peak seasons, undetermined optimal level of inventory. The lack of mathematical forecasting technique used was due to the lack of available data since the company has just started its plant operations. The group recommends the company to implement quantitative forecasting method for the demand of products, which can be either, be naive forecasting or multiplicative seasonal model incorporated with qualitative judgements. Monitoring and determining the accuracy of the forecasts should be made by the company as the years progress. The second problem, unoptimized production plan during peak seasons was traced to the lack of mathematical forecasting technique used. This could result to high production cost and no proper production schedule for the company. The group proposed a production plan alternative to be able to meet the demands during peak seasons and at the same time minimizes the cost of production. The third problem, undetermined inventory level, could incur high finished goods inventory holding cost which in turn result to high total cost for the company. For the stated problem, inventory plans were suggested. The stocking levels for the different ice cream flavors were suggested that would yield to the minimum cost for the company as well as meet the demands of the market. Other recommendations such as layout improvements, material requirements planning, and preventive maintenance were also given by the group. Implementation guidelines and other areas the company might want to study were suggested.